An Investigation of the Difficulties Faced by Syrian Asylum Seekers and Syrian Refugees in Acquiring a Second Language and the Possible Solutions from Refugees’ Perspective - AL MASRI, HAYAT MUHAMMAD GAZY (2018)
The current dissertation sheds light on the difficulties that Syrian refugees and asylum seekers face in acquiring the languages of the countries they had to flee to. To do so, this qualitative research investigated the experience of 45 Syrian refugees and asylum seekers who were hosted by 9 different countries around the world (Germany, Turkey, Sweden, Denmark, Norway, France, Malay, Austria, Romania); it concentrated on the difficulties that these refugees encountered in acquiring the languages of the hosting countries. It also sought to know the possible remedies and solutions for these difficulties from the participants’ point of view. Moreover, this research was executed on the Facebook messenger application through interviews and a survey with open-ended questions. The uniqueness of this research lies in the fact that it is studying the experience of refugees of one nationality, that are trying to acquire different languages not only one as it is the norm in the research. Finally, regarding the difficulties faced by asylum seekers and refugees in acquiring a second language, this research found that the main difficulty is caused by the language itself, along with the social, financial, temporal and psychological difficulties faced by the participants. As for the proposed solutions for these difficulties, the participants classified them into two categories: some of them were recommended to be made by the refugees themselves like practicing the acquired language and interacting with the native speakers in all the possible means; while the other solutions were recommended to be done by the governments of the hosting countries to encourage their nations to integrate more with the refugees to help them acquire the target languages.